2012
DOI: 10.2500/aap.2012.33.3613
|View full text |Cite
|
Sign up to set email alerts
|

Emergency department treatment of adults with acute asthma exacerbations: Effect on exhaled nitric oxide levels

Abstract: Measurement of exhaled nitric oxide levels (eNO) from asthmatic patients is a noninvasive marker of airway inflammation in both adults and children and has been used as an outpatient measure of asthma control. We examined eNO in acute asthma exacerbations and how it is affected by treatment in the emergency department (ED) setting. Both eNO and peak expiratory flow (PEF) rate were measured at arrival and before discharge for adult asthmatic subjects (n = 28) treated for acute exacerbations in the ED at Kings … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Fractional exhaled nitric oxide (FeNO) is a non-invasive, widely used method for assessing the inflammatory status of the lungs with airway disease [ 30 , 31 , 32 , 33 ]. It has achieved great consideration in the diagnosis of respiratory diseases and become highly popular parameter both in respiratory researchers and clinicians.…”
Section: Discussionmentioning
confidence: 99%
“…Fractional exhaled nitric oxide (FeNO) is a non-invasive, widely used method for assessing the inflammatory status of the lungs with airway disease [ 30 , 31 , 32 , 33 ]. It has achieved great consideration in the diagnosis of respiratory diseases and become highly popular parameter both in respiratory researchers and clinicians.…”
Section: Discussionmentioning
confidence: 99%
“…Should the asthma worsen, such a relatively large ACQ score increase could potentially be classified as a moderate exacerbation according to ATS/ERS recommendations [24]. Previous studies have already reported a paradoxical parallel increase in FEV1 and FENO during the recovery phase of an acute severe exacerbation [25,26]. Opposite FENO-FEV1 moves were not reported in those studies that involved relatively small numbers of patients, who experienced severe rather than moderate exacerbation.…”
Section: Discussionmentioning
confidence: 71%